El proceso de descentralización fiscal y su impacto en los gobiernos subnacionales - Chávez Tortorel, Vicente Segundo (2009)
This thesis addresses the issue of fiscal decentralization within a global vision that is, the process described, is immersed in the process of decentralization and reform of the State, likewise, raises the distinction between decentralization fiscal and economic decentralization. Looking at the process of fiscal decentralization, in the La Libertad Region: Regional Government, from the three basic ideas that the doctrine states: Resource Allocation, Decentralization of spending and borrowing, as well as the regulatory framework in the country, concluding that this process is not well developed in this regional structure, and in this regard, funding for services, construction and running costs, is through budgetary transfers and allocation of resources of the Regional Comprehension